Mapping static core-holes and ring-currents with X-ray scattering. (19th February 2021) - Moreno Carrascosa, Andrés; Yang, Mengqi; Yong, Haiwang; Ma, Lingyu; Kirrander, Adam; Weber, Peter M.; Lopata, Kenneth
Abstract : Quantum chemistry simulations in conjunction with scattering theory are used to demonstrate how static core-holes and attosecond valence electron currents manifest as measurable X-ray scattering modulations. Abstract : Measuring the attosecond movement of electrons in molecules is challenging due to the high temporal and spatial resolutions required. X-ray scattering-based methods are promising, but many questions remain concerning the sensitivity of the scattering signals to changes in density, as well as the means of reconstructing the dynamics from these signals. In this paper, we present simulations of stationary core-holes and electron dynamics following inner-shell ionization of the oxazole molecule. Using a combination of time-dependent density functional theory simulations along with X-ray scattering theory, we demonstrate that the sudden core-hole ionization produces a significant change in the X-ray scattering response and how the electron currents across the molecule should manifest as measurable modulations to the time dependent X-ray scattering signal. This suggests that X-ray scattering is a viable probe for measuring electronic processes at time scales faster than nuclear motion.